2014
DOI: 10.1371/journal.pone.0097834
|View full text |Cite
|
Sign up to set email alerts
|

Weight-Loss Strategies Used by the General Population: How Are They Perceived?

Abstract: BackgroundThe rising prevalence of obesity and the social pressure for thinness increase the prevalence of dieting. However, little is known about the overall perception of dieting strategies actually used by the general population.ObjectivesOur main objective was to investigate perceptions of weight-loss practices in an observational study in order to identify the most favourable strategy.DesignAdults from the ongoing Nutrinet-Santé cohort study who had reported engaging in dieting in the three previous years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
35
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 48 publications
2
35
0
1
Order By: Relevance
“…A lower FSA-NPS DI was associated with higher BMI and lower educational level in the cross-sectional crude analyses presented in Table 1. Regarding BMI, this result is consistent with the findings observed in other cross-sectional investigations on BMI and diet quality (48) and is probably due to the fact that overweight/obese people are more likely to be aware of nutritional recommendations or to be dieting (49) . Regarding educational level, the association with FSA-NPS DI was not statistically significant in a multivariate model including all the descriptors of Table 1 (P = 0•2, data not shown).…”
Section: Discussionsupporting
confidence: 91%
“…A lower FSA-NPS DI was associated with higher BMI and lower educational level in the cross-sectional crude analyses presented in Table 1. Regarding BMI, this result is consistent with the findings observed in other cross-sectional investigations on BMI and diet quality (48) and is probably due to the fact that overweight/obese people are more likely to be aware of nutritional recommendations or to be dieting (49) . Regarding educational level, the association with FSA-NPS DI was not statistically significant in a multivariate model including all the descriptors of Table 1 (P = 0•2, data not shown).…”
Section: Discussionsupporting
confidence: 91%
“…Since 80’s, restrictive diets to lose weight have been the subject of growing interest for the public, with a continuously raising number of specific diets proposed . Several studies have investigated the determinants of such practices in the general population; however, to our knowledge, none has done so among cancer survivors. Overweight and obesity have been recognized as risk factors associated with poorer cancer prognosis, cancer recurrence and second primary cancer, as well as with other health conditions such as cardiometabolic disorders .…”
Section: Discussionmentioning
confidence: 99%
“…Beside the fact that gluten avoiders exhibited higher energy intake, several hypothesis can explain this finding: first, many studies reported that people who avoid gluten often declared weight control as motives (12,13,17,18) . It is possible that these participants who avoid gluten to lose weight are therefore overweight (41) . A second hypothesis would be the consumption of gluten-free substitutes, known to contain more energy, carbohydrates, Na and lipids (21) .…”
Section: Discussionmentioning
confidence: 99%